Patterns of Chinese Male and Female Poetry: the cicada image from the Pre-Qin period(before 221 BC) to the Song Dynasty (960–1279) - Dashchenko, Hanna (Respectus Philologicus, 2025)
The paper focuses on the patterns of Chinese male and female poetry with the cicada image from the Pre-Qin period (先秦, before 221 BC) to the Song dynasty (宋朝, 960–1279). The relevance of the study is determined by the dearth of works on the cicada image in classical Chinese poetry as well as by the gender bias. This paper fills in the underexplored aspect of the existing literature by tracing the evolution of the cicada image in poetry from the Pre-Qing period to the Song dynasty. The female perspective allows us to reveal the gendered patterns of cicada symbolism in classical Chinese poetry, deconstruct the processes of male dominance and restore the overlooked female contributions. The paper shows that in male poetry, the cicada is considered as a symbol of: 1) resurrection, longevity, and hope of rebirth; 2) hot summer; 3) people dissatisfied with their ruler; 4) an honest official; 5) purity. In female poetry, the cicada image is used as a harbinger of death; a symbol of an official who pursues his own goals and cares only about his benefit; cicadas’ chirping is associated with sorrow, longing, and anxiety. Two groups of female poems were identified depending on the way the emotions are depicted. The “implicit” group includes poems where the cicadas’ chirping becomes an eloquent detail and is associated with sorrow, longing, and anxiety. Still, the emotions of the lyrical persona are not directly mentioned. The “explicit” group includes poems where the cicadas’ chirping acts as a trigger for the uncontrolled emotional reaction of the lyrical persona.